Response of training participants in preparation of argumentative questions to train HOTS in Davao Indonesian school teachers - Rinie Pratiwi Puspitawati; Fida Rachmadiarti; Widowati Budijastuti; I. Isnawati; Reni Ambarwati; Pramita Yakub; Indra Tejamukti (Journal of Community Service and Empowerment, 2024)
Higher-Order Thinking Skills (HOTS) can be trained through concepts in science learning generally, and biology in particular. Teacher competence to facilitate students skilled HOTS can be improved through scientific forums, one of which is training and workshops. This activity is an alternative for teachers to refresh their understanding and pedagogical skills and build enthusiasm through various modeling and information to generate motivation. Training activities on the preparation of argumentative questions to train HOTS for Davao Indonesian School Teachers of Philippines were held in two stages, the first stage was carried out synchronously through online meetings using Zoom Meeting, while in the second stage, training was carried out asynchronously using Google Classroom. Trainees' responses to the implementation of the training were netted with an online questionnaire using Google Form. The data were analyzed in a quantitative descriptive. The results of this study showed that all participants rated that the material presented by the resource persons was good, which included material on HOTS, STEM approaches, and argumentative thinking. In addition, participants also gave positive responses to the workshop on developing argumentative questions, the ability of resource persons, and the technical implementation of the training. Participants hope that this activity can be followed up with offline training.